The preparedness of schools in responding to emerging climate change impacts and risks in Bhutan: A Bourdieusian analysis - Thapa, Ramesh; Gough, Annette; Cooper, Grant (2024)
Climate change is accelerating, and it is becoming clearer that the education sector in countries around the world will bear the brunt of the effects. Research into the impacts of climate change on schools and children as well as their engagement in responses is still sparse, albeit growing. In this paper, Bourdieu’s concepts of field, habitus, and capital are applied to better understand the practice of school climate response and the role schools may have in climate action. The analysis is based on interviews with Bhutanese school leaders, teachers, and district education officials. The results indicated that the school system and learners experienced multiple impacts and shocks. Opportunities to engage in practices for climate response were constrained by access to capital (cultural & economic) and policy and institutional structures. Socio-cultural dispositions showed a noteworthy influence on school stakeholders’ engagement in environmental and climate response interventions. Social capital acted as a catalyst for initiating environmental and climate change actions, carried out through collective school, community, and student-based activities. This research adds to the literature by exploring opportunities for social transformation that may lead to more effective practices in school climate action and more broadly, the scope of Bhutanese schools to respond to socio-scientific issues in science education.